Strategies for Improving Foreign Worker Productivity: Construction Manager Perspective - Nurhafiffi, Sukri; Rahimi, A. Rahman (AIP Publishing, 2023)
In line with the development of the construction sector, the shortage of construction workers is becoming a chronic problem that most construction companies face. Therefore, construction industries are employing foreign workers to cater to the demand. However, the use of foreign workers has caused several problems for construction companies because of their low productivity and poor quality of works. This study identifies management strategies for improving construction labor productivity of foreign workers and challenges to implementing those strategies. To achieve these objectives, the data collection involves individual interviews with 20 construction managers. The data is then analyzed using the thematic analysis technique. This study’s findings suggest that the strategies for improving foreign workers’ construction labor productivity include education, training, and mentoring. On the other hand, the challenges to implementing those strategies are lack of training resources, difficulty to satisfy training requirements, and mentor’s limited ability. Researchers and industry practitioners may employ these findings to improve existing plans and develop new policies to improve the construction labor productivity of foreign workers.